The Impact of a Video-Assisted Teaching Program on the Prevention of Homicide Among Undergraduate Nursing Students at Selected Nursing Colleges in Bagalkot - Pradeep M.; Chetan Sangati (International Journal of Evidence Based Nursing And Practices, 2025)
Nomophobia, or the fear of being without a mobile phone, has emerged as a prevalent psychological concern in the 21st century, significantly affecting individuals' mental well-being, particularly among younger populations. This phobia can lead to feelings of anxiety, stress, and even depression, resulting from the constant dependence on mobile devices for communication and social interaction. The study aimed to evaluate the effectiveness of a video-assisted teaching program in preventing nomophobia among undergraduate nursing students in Bagalkot. The study involved 80 nursing students who were assessed using a pre-test and post-test to evaluate their knowledge regarding the symptoms, causes, and potential consequences of nomophobia. The participants were then exposed to a video-assisted teaching program, which provided detailed information about the psychological aspects of nomophobia, strategies for managing mobile device usage, and the importance of maintaining a healthy balance between technology use and personal well-being. After the intervention, the post-test scores revealed a statistically significant improvement in the participants' knowledge compared to their pre-test scores, indicating that the video-assisted teaching program was effective in increasing awareness and understanding of nomophobia. The findings suggest that such educational interventions could be beneficial in reducing the fear and anxiety associated with excessive mobile phone use, particularly in vulnerable groups like nursing students who may experience heightened stress due to academic pressures. This study highlights the potential of multimedia-based educational strategies in promoting mental health awareness and providing preventive measures against technology-related psychological issues like nomophobia. In conclusion, the video-assisted teaching program demonstrated significant effectiveness in enhancing knowledge and potentially mitigating the negative effects of nomophobia, offering a promising approach for similar interventions in other educational settings.
Keywords: Nomophobia; mental health awareness; mobile phone addiction; nursing students; video-assisted teaching